1995
DOI: 10.1677/joe.0.1440135
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for chromium acting as an essential trace element in insulin-dependent glucose uptake in cultured mouse myotubes

Abstract: Previous work from this and other laboratories has suggested that the trace element chromium plays some role in glucose homeostasis. In this study, we sought to characterise an in vitro cell culture model in which the effects of chromium on insulin-dependent glucose uptake could be studied. Mouse C2C12 myoblasts were differentiated to form myotubes in culture in chromium-replete or chromium-poor media. Chromium levels in standard media were 0.56 +/- 0.01 micrograms/l (mean +/- S.E.M.) compared with 0.09 +/- 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 0 publications
2
12
0
Order By: Relevance
“…The relative enhancing effect of metformin was higher in cells incubated in 25 mM glucose rather than in 5 mM glucose, consistent with its selective action in hyperglycemic conditions in vivo [30,32]. As reported for metformin [33][34][35][36], the effects of CrPic are not attributed to increased expression of GLUT4 protein but rather its translocation and/or activation state [18,[37][38][39]. Combined, these results predict that during the hyperglycemic state Cr 3+ may functionally enhance insulin action by targeting the plasma membrane.…”
Section: Introductionsupporting
confidence: 80%
“…The relative enhancing effect of metformin was higher in cells incubated in 25 mM glucose rather than in 5 mM glucose, consistent with its selective action in hyperglycemic conditions in vivo [30,32]. As reported for metformin [33][34][35][36], the effects of CrPic are not attributed to increased expression of GLUT4 protein but rather its translocation and/or activation state [18,[37][38][39]. Combined, these results predict that during the hyperglycemic state Cr 3+ may functionally enhance insulin action by targeting the plasma membrane.…”
Section: Introductionsupporting
confidence: 80%
“…The role of chromium in carbohydrate metabolism has been reported for both turkeys and humans (Levine et al 1968). It has been reported that organic chromium supplementation to diets of rats (Gray and Bowman 1992), mice (Morris et al 1995), chickens (Lien et al 1999) and feeder calves (Kegley and Spears 1995) had positive effects on glucose metabolism and insulin activity. Chromium has improved glucose tolerance in both experimental animals and man (Mertz 1969;Doisy et al 1976).…”
Section: Introductionmentioning
confidence: 99%
“…A growing number of studies from this and other laboratories [9][10][11] imply that chromium has a role to play in insulin action. We were able to clearly show with in vitro studies that a depletion of chromium significantly reduces the ability of insulin to stimulate glucose uptake: this sensitivity to insulin was restored when chromium concentrations were increased to "physiological" levels [12]. Does the increase in chromium excretion (and hence increased insulin resistance) result in an improved physiological response by some women to their pregnancy which ensures adequate supplies of glucose to the growing fetus?…”
Section: Discussionmentioning
confidence: 85%